PEMIKIRAN REAKTIF TENTANG HUKUM POLIGAMI DALAM AL-QUR'AN (PEMIKIRAN QURAISH SHIHAB DALAM TAFSIR AL-MISHBAH) - Norcahyono, Norcahyono (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
This research is motivated by the attitude of some people who are pros and cons toward the law of polygamy in the Qur'an. The researcher found that these two attitudes seem to counter to each other and mutually apathy. The pro-people tend to ease the poligamy and ignore its purpose, whereas, the cons reject the practice of polygamy under the excuse of being not ready. This research is conducted to answer to the pros and cons using the thoughts of Quraish Shihab as a mufassir and a Muslim scholars. This research is expected to be able provide a full understanding of polygamy in the Qur'an. This is a literature study. The research object is the reactive thoughts of Quraish Shihab and the source is Tafsir al-Mishbah. From this research it can be seen that, polygamy offered in the Qur'an does not mean without limits, terms, and purpose. Likewise, The Quran does not ban poligamy if it is as an emergency solution to a particular case, and only those who have the knowledge and capability are allowed to do poligamy.